Ruptured Renal Angiomyolipoma - Sébastien Azzi; Patrice Jissendi; Fadi Tannouri (Journal of the Belgian Society of Radiology, 2022)
Teaching Point: This case highlights the importance of extending the medical analysis to other areas with lumbar computed tomography, especially to the kidneys and the retroperitoneum.